2018
DOI: 10.1139/cjm-2017-0755
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii infection induces the formation of host’s nuclear granules containing poly(A)-binding proteins

Abstract: To study the mechanism by which human host cells respond to an infection of Toxoplasma gondii, we monitored the level of poly(A)-binding protein (PABP), an indicator of translation. Here, we report an observation of the relocalization of PABPs in human host cells upon T. gondii infection. Notably, the aggregates of PABPs formed upon infection are mainly found in the nucleus, which is a different response from that found after exposure to heat shock. Pyrimethamine treatment of the infected monolayers inhibits t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Translational control is also achieved via trans-regulatory factors, such as RNA-binding proteins, microRNAs, and "specialized ribosomes" (93)(94)(95). A recent study by Fischer and colleagues reported that infection by T. gondii causes the formation of stress granules containing poly(A)-binding proteins (PABPs) in the nucleus of the host cell (96). PABPs regulate several steps in mRNA processing, such as export, degradation, stability, polyadenylation, and deadenylation (97,98).…”
Section: Discussionmentioning
confidence: 99%
“…Translational control is also achieved via trans-regulatory factors, such as RNA-binding proteins, microRNAs, and "specialized ribosomes" (93)(94)(95). A recent study by Fischer and colleagues reported that infection by T. gondii causes the formation of stress granules containing poly(A)-binding proteins (PABPs) in the nucleus of the host cell (96). PABPs regulate several steps in mRNA processing, such as export, degradation, stability, polyadenylation, and deadenylation (97,98).…”
Section: Discussionmentioning
confidence: 99%
“…Poly-adenosine-binding proteins (PABPs) are RNA binding proteins that bind to polyadenylated RNA and are involved in metabolic pathways of the mRNA, and their sub-cellular distribution changes in response to cellular stress (Gray et al, 2015). Nuclear granulation of PABPs is induced in T. gondii -infected HFFs (Fischer et al, 2018), which may enable the parasite to influence the host cell transcriptome. Quantitative proteomic analysis of HFFs also indicates that T. gondii globally reprograms key metabolic pathways in the host cell, including glycolysis, lipid, and sterol metabolism, mitosis, apoptosis, and structural-protein expression (Nelson et al, 2008).…”
Section: Host Innate Immunity To T Gondii Infectionmentioning
confidence: 99%